The Role of Arbitration Institutions In Resolution of Investment Disputes In Indonesia (Case Study on PT Ferrostaal AG Against PT. Nusantara III regarding Violation of Joint Venture Agreement) - Nanda Utama (Ekasakti Journal of Law and Justice, 2025)
Arbitration comes from the word "arbitrare" which means "the power to resolve a case according to policy. From the definition of arbitration, it is a policy indicating that there is a forum for resolving business disputes for parties who are wiser in finding a fair solution. H. M. N Poerwosutjipto uses the term arbitration which can be interpreted as a peace court, where the parties agree that disputes regarding personal rights that they can fully control are examined and tried by an impartial judge and the decision is binding on both parties.   On the other hand, the speed and effectiveness of dispute resolution through arbitration can also be done simply and informally, meaning it can only be determined by the parties to the dispute. The role of arbitration in carrying out legal functions and ensuring justice is seen in its authority, such as its ability to make decisions and encourage peace. The effectiveness of making decisions in dispute resolution through arbitration has been tested and is able to provide a meeting point to reach an agreement without having to sacrifice one of the parties to the dispute. Optimizing the success of dispute resolution through arbitration requires the parties to have a sense of good faith. The results of this study explain that, first, the role of arbitration in business investment disputes can be carried out in the realm of losses from one party in civil law in terms of lost profits and return those profits through the imposition of penalties to pay losses from the respondent itself. Second, the effectiveness of dispute resolution through arbitration forums is able to prove legal facts quickly and accurately so that PTPN III as a local Indonesian company is not proven guilty. In this regard, the arbitration forum is independent and cannot be intervened by any other party except the disputing parties. The author recommends the need for other legal guarantees. Therefore, in relation to this matter, legal, political, and security guarantees must be provided to the maximum by the Indonesian government because these guarantees are what the Indonesian government should offer if there is a desire to attract as many investors as possible.